The impact of institutionalised governance on IT project management. - Goh, Koon Ngee. (2009)
The management of IT projects has frequently centred on the delivery of solutions within time, budget and scope. The benefits derived from such a focus need to be view in the context of the organisation. The research looked at frameworks such as ISO 38500, COBIT and CMMI and mapped them to each other to demonstrate their relevance to governance efforts. By using these frameworks, the research looks at how institutionalised governance impacts the delivery of IT’s business value through the evaluation of various published case studies, it is seen that governance initiatives usually arise from audit or regulatory requirements and institutionalising governance within the organisation helps the achievement of quality deliverables while those without such control mechanisms typically reported sub-optimal performance.